Aerobic Bacteria Abundance and Mineral Elements Status in Aged and New Culture Ponds of Tiger Shrimp (Penaeus Monodon) - Ismaun, Hamidah (2006)
The shrimp farming in Malaysia is a rapidly developing industry. However, in recent years, the production of cultured shrimp has decreased due to the unsustainable farming practices that lead to outbreaks of diseases. Thus, a comparative study was carried out to analyze the bacterial abundance in aged and new culture ponds of Penaeus monodon situated in Merlimau, Malacca.